Performance of Desi X Exotic Cross-Bred Layers - Jayanthy MV (Department of Poultry Science, College of Veterinary Science, 1992)
Data were collected on egg production performance of two cross-breds viz. desi X Austra White (DAW) and desi X New Rock (DNR) from 20 to 40 weeks of age. The birds in each cross consisted of naked neck and normal neck varieties. DNR cross birds were significantly heavier at 20 and 40 weeks of age than DAW cross birds. The body weight in Naked neck and normal neck varieties comparable in both crosses. Age at sexual maturity was 184 and 189 days in DNR and DAW crosses respectively. Hen housed and hen day egg numbers were similar in both crosses (37.61 and 47.61 vs 34.40 and 47.81), while the naked neck birds in both crosses showed higher hen housed and hen day egg number between the varieties in DAW cross was significant (53.82 Vs 34.86). The eggs were significantly heavier in DNR cross than in DAW cross (46.74 Vs 44.88) whereas the varieties with in both crosses laid eggs of similar size. The mean daily feed consumption and feed efficiency were also similar in both crosses (106.61 g and 4.09 Vs 104.95 g and 4.93). In DAW cross, the naked neck birds registered a better feed efficiency. While DNR birds were multicolored and laid brown eggs, DAW crosses consisted of only black, grayish white with black patches and grey birds which laid tinted eggs. Broodiness was observed in both the crosses. Egg quality was excellent in both the crosses and varieties with in crosses, at 32 weeks of age. Livability was also similar in both crosses though it was poor. Considering the overall performance, the DNR cross was adjudged as a better cross for the backyard.